2015
DOI: 10.1517/13543776.2014.1001738
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinedione compounds: a patent review (2010 – present)

Abstract: Diabetes management is very important as the number of diabetic patients increased and therefore the present research article will be very much useful for the development of new molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The thiazolidinedione-type drugs identified in this study, pioglitazone, rosiglitazone, hydroxypioglitazone, and mitoglitazone, were found to be inhibitors of eMST. They are known agonists of peroxisome proliferator-activated receptor g (PPARg) and have an antidiabetic therapeutic effect via the amelioration of insulin resistance (Desai et al, 2015). Recently, they have also been found to possess an antimicrobial effect for bacteria (Masadeh et al, 2011), although the underlying molecular mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The thiazolidinedione-type drugs identified in this study, pioglitazone, rosiglitazone, hydroxypioglitazone, and mitoglitazone, were found to be inhibitors of eMST. They are known agonists of peroxisome proliferator-activated receptor g (PPARg) and have an antidiabetic therapeutic effect via the amelioration of insulin resistance (Desai et al, 2015). Recently, they have also been found to possess an antimicrobial effect for bacteria (Masadeh et al, 2011), although the underlying molecular mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The PPAR γ controls fatty acid storage and glucose metabolism by coordinating the expression of genes involved in lipid metabolism, adipogenesis and inflammation . This receptor is activated by the thiazolidinedione (TZD) antidiabetic drugs . PPAR β / δ regulates fatty acid catabolism, insulin sensitivity and energy homeostasis in muscle and adipose tissue .…”
Section: Methodsmentioning
confidence: 99%
“…Only one kaempferol diglycoside kaempferitrin was reported to activate the insulin signaling pathway and stimulate secretion of adiponectin in 3T3-L1 adipocytes. Therefore, the insulin-like effects of two flavonol glycosides from C. osmophloeum leaves (CO-1 and CO-2), which are structurally different from previously reported kaempferitrin, were investigated on three of the proteins (adiponectin, IRβ and GLUT4) involved in insulin signal transduction pathway using mouse 3T3-L1 adipocytes [104].…”
Section: Cinnamomum Speciesmentioning
confidence: 99%